2016
DOI: 10.1159/000447430
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumomediastinum as a Potential Predictor of Mortality in Patients with Idiopathic Pulmonary Fibrosis

Abstract: control group included 36 IPF patients (28 males; median age: 69 years; VC% at baseline: 57%). In a multivariate Cox regression analysis, PM was a significant predictor of mortality [hazard ratio (HR): 3.0; p = 0.032]. Considering only patients experiencing PM at the time of IPF diagnosis (n = 4), PM was a strongly significant predictor of mortality in multivariate analysis (HR: 6.4; p = 0.007). Conclusions: Spontaneous PM is a rare but serious complication in patients with IPF and may be considered as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…SPM has been associated with many conditions and triggers, such as asthma exacerbation, severe cough or vomiting and other activities associated with the Valsalva maneuver [[2], [3], [4]]. Few case reports have shown that SPM has also occurred in patients with idiopathic pulmonary fibrosis and can be considered as a predictor of mortality [8]. No case of SPM associated with Henoch-Schonlein purpura has been published so far.…”
Section: Commentmentioning
confidence: 99%
“…SPM has been associated with many conditions and triggers, such as asthma exacerbation, severe cough or vomiting and other activities associated with the Valsalva maneuver [[2], [3], [4]]. Few case reports have shown that SPM has also occurred in patients with idiopathic pulmonary fibrosis and can be considered as a predictor of mortality [8]. No case of SPM associated with Henoch-Schonlein purpura has been published so far.…”
Section: Commentmentioning
confidence: 99%
“…In this cohort, most patients that had developed a pneumomediastinum experienced an increase in dyspnoea in the preceding weeks, however, no specific patient characteristics were associated with its occurrence as compared with controls (including age, gender, smoking history and severity of lung function). The mechanism is thought to be air leak due to sudden changes in intrathoracic pressure; this may occur on airway walls or in alveoli 4 . Treatment is generally conservative and in the cohort analysis often involved antibiotics or, when associated with an exacerbation, steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is thought to be air leak due to sudden changes in intrathoracic pressure; this may occur on airway walls or in alveoli. 4 Treatment is generally conservative and in the cohort analysis often involved antibiotics or, when associated with an exacerbation, steroids. Development of a pneumomediastinum was associated with a poorer prognosis (HR 6.4, p < 0.007 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation can generate a retractive process illustrated by the bronchiectasis and the pneumomediastinum. Such a phenomenon is also seen in acute exacerbation of idiopathic pulmonary fibrosis [4], pleuroparenchymal fibroelastosis or melanoma-differentiation-associated protein 5 related interstitial lung diseases [5]. The high speed of inflammation installation and lung architectural change in these conditions could possibly explain the onset of pneumomediastinum.…”
mentioning
confidence: 98%
“…3 Intensive Care Unit, Avicenne Hospital, AP-HP, Bobigny, France. 4 Sorbonne Paris Nord University, Bobigny, France. 5 Infectious Diseases Dept, Avicenne Hospital, AP-HP, Bobigny, France.…”
mentioning
confidence: 99%